STUDI POTENSI PENGOMPOSAN SAMPAH KOTA SEBAGAI SALAH SATU ALTERNATIF PENGELOLAAN SAMPAH DI TPA DENGAN MENGUNAKAN AKTIVATOR EM4 (EFFECTIVE MICROORGANISM) - Budihardjo, Mochamad Arief (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2006)
In  general,  waste  management  in  most  of  City  in  Indonesia  still  boundary  on collecting, transporting  and  dumping.  Solid  waste  are    collected,  transported  and  pulled  up  in landfill without any treatment. Needed a new paradigm that landfill is not a final estuary of city waste but place management of city waste. One of the problem faced is amount arise of organics city waste. Starting from this situation hence needed handling to arising organic waste. Composting represent  one  of  the  alternative  in  the  effort    to  reduce  the  amount  of  organics city  waste through  the  make  up  of  value  utilize  waste  become  worthwhile  compost  as fertilizer.  Natural composting of organics waste took a time to process. Effective microorganism (EM4) applicated in  organics  waste  composting  in  landfill  is  used  to  speed  up  compost  decomposition and improve the compost quality. Composting use all kinds of city waste that enter to the landfill, like residue of vegetables, fruits, leaves and sawmill waste. Composting city waste wrap up addition material that  is sawdust and  cow  manure. At this research, compost  variation  include natural control variation, organic waste and EM4, organic waste : sawdust and EM4 with comparation 7:3; 1:2; 5:7; 5:4 and 7:6. Organic waste:  cow manure and EM4 with comparition 1:2; 2:5; 6:5 and 7:6. Result of this research indicate that the overall compost variation has fulfilled standard of  quality  matured  compost  according to  SNI  19-7030-2004t.  Compost  with  EM4  has relative good  quality  than  natural  compost.  Besides,  overall  of  compost  variation  have  fulfilled hara standard of crop requirements, low cost of producing and yield high level of city waste reducing. Compost  variation of 7 organic city waste : 3 sawdust represent  most applicable composition compost  at  Boyolali  landfill  with  C-organic  24,52  %,  N-total  1,72  %,  Ratio  C/N 14,25,  P-total 1,20 %, K-total 1,66 %, Temperature 27,70 0C and pH 7,30 also compost level reduction 61,6 %.